2009
DOI: 10.4315/0362-028x-72.2.384
|View full text |Cite
|
Sign up to set email alerts
|

Certified Kitchen Managers: Do They Improve Restaurant Inspection Outcomes?

Abstract: Restaurants are associated with a significant number of foodborne illness outbreaks in the United States. Certification of kitchen managers through an accredited training and testing program may help improve food safety practices and thus prevent foodborne illness. In this study, relationships between the results of routine restaurant inspections and the presence of a certified kitchen manager (CKM) were examined. We analyzed data for 4,461 restaurants in Iowa that were inspected during 2005 and 2006 (8,338 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 11 publications
1
30
1
1
Order By: Relevance
“…This finding disagrees with that of Hedberg et al (8), who reported that a certified kitchen manager was more likely to be present in restaurants that did not have outbreaks. In a more recent study, the authors also suggested that the presence of a certified manager was protective for most types of recorded violations (2). Despite a lack of significance (P < 0.05) in the present study, violations related to the presence of a certified manager were detected 11 % of the time in outbreak inspections and 24% of the time in routine inspections and should be given more importance based on previous work.…”
Section: Resultscontrasting
confidence: 65%
“…This finding disagrees with that of Hedberg et al (8), who reported that a certified kitchen manager was more likely to be present in restaurants that did not have outbreaks. In a more recent study, the authors also suggested that the presence of a certified manager was protective for most types of recorded violations (2). Despite a lack of significance (P < 0.05) in the present study, violations related to the presence of a certified manager were detected 11 % of the time in outbreak inspections and 24% of the time in routine inspections and should be given more importance based on previous work.…”
Section: Resultscontrasting
confidence: 65%
“…Due to the number of people affected annually and the economic losses that are caused, foodborne diseases still continue to be a major public health concern in developed countries (Cates et al, 2009;Scharff, McDowell, & Medeiros, 2009;Senior, 2009;WHO, 2007;Medeiros et al, 2004;WHO, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…One of the risk factors for which the presence of a certifi ed food protection manager had the most positive correlation in restaurants and deli retail stores was poor personal hygiene. Other studies support these results by showing that restaurants with a CKM present were less likely to have critical violations than those without a CKM (Cates et al ., 2009 ;Kassa et al ., 2010 ).…”
Section: Current Knowledge and Hygiene Practices Among Food Handlersmentioning
confidence: 66%